Self-reported carbohydrate supercompensation and supplementation strategies adopted by Olympic triathlon athletes - Mendes, M. P.; Marinho, A. H.; Moura, F. A.; Bádue, G. S.; Ferreira, G. A.; de Araujo, G. G.; Lima-Silva, A. E.; Ataide-Silva, T. (Brazilian Journal of Medical and Biological Research, 2025)
The aim of the present study was to describe the use of tapering, carbohydrate (CHO) supercompensation, and supplementation strategies self-reported by athletes in the Olympic triathlon category. A total of 72 triathletes (61 males and 11 females) answered an online questionnaire about their training and performance, supercompensation strategies, carbohydrate supplementation, and use of supplements and other ergogenic substances. The information was summarized and subjected to descriptive analysis. Shapiro-Wilk test was applied to check data normality. The t-test was used to investigate differences in the analyzed variables between sexes. Almost all triathletes reported to have performed tapering (93.05%) and approximately half of them adopted a CHO supercompensation strategy (48.61%); updated CHO supercompensation was the most used strategy (27.77%). Most participants (86.11%) used CHO supplementation during competitions, but in amounts below the 60 g/h recommended for most athletes (96.77%). Thus, since few triathletes performed supercompensation, in addition to the insufficient amount of supplemented carbohydrate taken by them, it could be concluded that triathletes were not sufficiently aware of nutritional recommendations or did not adopt them.